Identification of Core Genes Related to Progression and Prognosis of Hepatocellular Carcinoma and Small-Molecule Drug Predication - Jiang, Nan; Zhang, Xinzhuo; Qin, Dalian; Yang, Jing; Wu, Anguo; Wang, Long; Sun, Yueshan; Li, Hong; Shen, Xin; Lin, Jing; Kantawong, Fahsai; Wu, Jianming (Frontiers in Genetics, 2021)
Background: Hepatocellular carcinoma (HCC) is one of the most leading cause of cancer death with a poor prognosis. However, the underlying molecular mechanisms are largely unclear and effective treatment for it is limited. Using an integrated bioinformatics method, present study aimed to identify the key candidate prognostic genes that are involved in HCC development and identify small molecule drugs with treatment potential. Methods and results: In this study, by using three expression profile datasets from Gene Expression Omnibus database, 1704 differentially expressed genes were identified, including 671 upregulated and 1033 downregulated genes. Then, weighted co-expression network analysis revealed 9 modules are related with pathological stage, turquoise module was the most associated module. Gene ontology and Kyoto Encyclopedia of Gene and Genome pathway analyses indicated that these genes were enriched in cell division, cell cycle and metabolic related pathways. Furthermore, by analyzing the turquoise module, 22 genes were identified as hub genes. Based on HCC data from GEPIA database, 9 genes associated with progression and prognosis of HCC were screened, including ANLN, BIRC5, BUB1B, CDC20, CDCA5, CDK1, NCAPG, NEK2, and TOP2A. According to the Human Protein Atlas and the Oncomine database, these genes were highly upregulated in HCC tumor samples. Moreover, multivariate Cox regression analysis shown that the risk score based on the gene expression signature of these 9 genes was an independent prognostic factor for overall survival and disease-free survival in HCC patients. In addition, the candidate small molecule drugs for HCC were identified by the CMap database. Conclusion: In conclusion, the prognostic 9-genes signature was identified and validated in prognosis of HCC. Moreover, several candidate small molecule drugs may contribute to HCC treatment.